Simulation Analysis of the Motion of Superparamagnetic Particles in Liquid-Phase Fluid under a Magnetic Field - Qiangqiang Zhang; Hui Song; Ruhong Song; Xianguo Hu (Applied Sciences, 2023)
Based on the magnetic response of magnetic particles, the targeting of particles to a target area under the modulation of an external magnetic field has been used in many applications. An accurate kinematic model is helpful to achieve accurate targeting of magnetic particles and to investigate the factors influencing the motion of the particles. In the present paper, a segmental magnetization model was proposed based on the real magnetization process of superparamagnetic particles to calculate the magnetic force, and this was compared with a traditional magnetization model. The effects of magnetic field strength and particle diameter on the trajectory of magnetic particles in fluids under a magnetic field were further analyzed using a finite element analysis software. The simulation results show that changing the particle size only affected the velocity of the particles and did not affect the trajectory. When magnetic field strength changed, magnetic particles showed different trajectories. Notably, when the magnetic field force in the Y direction was too large, meaning the gravity could be neglected, the trajectory of the particles no longer changed when the magnetic field strength was varied.